PSVII-6 Relationship between placentome location and gene expression in bovine pregnancy. (7th December 2018) - MacConnell, E; Trubenbach, L; Wickersham, T; Sawyer, J; Satterfield, M
Abstract: We recently developed a novel non-terminal surgical technique to remove single placentomes from the pregnant ewe for gene expression and histological analyses. This technique allows evaluation of nutritional insults on placental development at more than one stage of gestation. However, the question remained of whether placentome gene expression varies based on location relative to the fetus. While this technique has not been developed in cattle, the similar shape of the bovine and ovine placenta led to this study in heifers. Pregnant heifers were maintained on forage during early gestation and later moved into a Calan gate system (American Calan, Northwood, NH). On gestational day (GD)158, five heifers were assigned to receive a hay diet formulated to meet 100% of maintenance requirements, and five heifers were fed 70% of maintenance requirements until necropsy on GD270. At necropsy, a single representative placentome was selected from the antimesometrial side of 1) the gravid horn central to the amnion, 2) over the allantois immediately adjacent to the amnion, 3) in the tip of the gravid horn, and finally 4) in the tip of the contralateral horn. Placentomes were removed, weighed, finely minced, snap frozen in liquid nitrogen and stored at –80 o C until Real Time qPCR analysis. Mean weight of placentomes was greater (PFGF2, ODC1, VEGFA, and FLT1), nutrient transporters (SLC7A1, and SLC2A1 ), and factors associated with hormone action (ESR1, IGF1, IGFBP3, CSH1, and PAG1 ) were unaffected (P > 0.05) by dietary treatment or location of the placentome. Results indicate that location of the placentome in relation to the fetus does not impact gene expression, enhancing the efficacy of non-terminal placental sampling methodologies.